Synchronization of pulsed and continuous-wave IMPATT oscillators in the millimeter wavelength range. Part 2. Stabilizing microwave parameters of synchronized generators - Mykola Karushkin (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
This is the second part of the two-part article, which summarizes the state-of-the-art results in the development of synchronized oscillators based on IMPATT (IMPact ionization Avalanche Transit-Time) diodes. The first part of the paper presented the electrodynamic design of oscillators, which contain a resonant oscillatory system with silicon IMPATT diodes and are synchronized by an external source of microwave oscillations. The second part of the paper considers the methods for stabilizing the parameters of IMPATT oscillators, which make it possible to create coherent power sources in the millimeter wavelength range. The specifics of pulse generators lies in the change in frequency within the microwave pulse relative to the change in temperature, which leads to a change in the impedance of the diode and thus to a phase change with respect to the synchronizing signal. Phase modulation is reduced or completely eliminated (which is necessary to ensure the coherence of the microwave transmitter) by using current compensation, i.e., by using the control current pulse with a special shape. The study demonstrates the expediency of introducing additional heating of the semiconductor structure of the IMPATT diode, which allows the initial temperature of the IMPATT diode in the region of the leading edge of each pulse to remain virtually constant and independent of the ambient temperature. Using these methods on silicon double-drift IMPATT diodes allowed creating synchronized oscillators with high frequency stability and an output power level from 20 to 150 W, which have a high degree of coherence in the synchronization mode with an external signal. The paper also presents the designs and parameters of coherent microwave power sources in the short-wave part of the millimeter wavelength range using the nonlinear properties of the IMPATT diodes in the radio-pulse conversion mode. This mode makes it possible to provide the output power level of the signal at the n-th harmonic Pout ≈1/n, which significantly exceeds the achieved characteristics of the frequency multipliers with charge accumulation, where Pout ≈ 1/n2. The output power of such devices is achieved at the level of 50–20 mW in the 75–180 GHz frequency range with a frequency multiplication factor of 1–15.